2020
DOI: 10.1038/s41467-020-16807-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic breakdown of a Tet-off conditional lethality system for insect population control

Abstract: Genetically modified conditional lethal strains have been created to improve the control of insect pest populations damaging to human health and agriculture. However, understanding the potential for the genetic breakdown of lethality systems by rare spontaneous mutations, or selection for inherent suppressors, is critical since field release studies are in progress. This knowledge gap was addressed in a Drosophila tetracycline-suppressible embryonic lethality system by analyzing the frequency and structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…We discuss and demonstrate methods to mitigate some of these resistance mechanisms in previous publications ( Maselko et al, 2017 ; Maselko et al, 2020 ). Recently, published work describes instances where such resistance mutations can arise reproducibly at very low frequencies ( Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We discuss and demonstrate methods to mitigate some of these resistance mechanisms in previous publications ( Maselko et al, 2017 ; Maselko et al, 2020 ). Recently, published work describes instances where such resistance mutations can arise reproducibly at very low frequencies ( Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the decision of releasing fertile strains should be carefully evaluated since the resistance to the lethality systems could arise. Recent studies showed that spontaneous mutations in a genetic strain could lead to the buildup of revertants, and in addition, a pre-existing inherent variation in the targeted field population could suppress the lethal system of an effector gene 47 , 48 . Nevertheless, FK approach can be used to produce male-only population and prevent the collateral damage to the fruits compared to a bi-sexual release, in which females can still damage fruits and lead to subsequent infestations even if they are sterilized 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional switch is a useful technology in regulating the expression of target genes, especially essential genes. The most popular transcriptional switches are tet-off, , phl-off, cym-off, cam-off, , etc. In this study, we designed an Agm1-on/off switch based on the cam-off system to regulate the expression level of the AGM1 gene and attempted reprogramming the metabolic network in K.…”
Section: Results and Discussionmentioning
confidence: 99%